Analisis Peran dan Strategi Persatuan Tunanetra Indonesia (PERTUNI) dalam Meningkatkan Kemandirian Perekonomian Masyarakat Penyandang Tunanetra (Studi kasus Kota Medan) - Dessy Rahmadani; Annio Indah Lestari Nasution; Atika Atika (Trending: Jurnal Manajemen dan Ekonomi, 2025)
This study aims to (1) find out what are the roles and strategies of Pertuni in improving the economy of the blind community (2) find out how the roles and strategies of Pertuni in empowering the blind community (3) Know the obstacles in implementing the Pertuni program. As well as, (4) knowing the results of the study of Pertuni's roles and strategies in improving the economy and empowering the blind community with SWOT analysis. This research uses descriptive qualitative methods and information obtained with SWOT analysis. The results showed that (1) the role and strategy of Pertuni in improving the economy by holding various kinds of training such as pre-employment soft skills training, entrepreneurship, holding family gathering activities, and having a side business. (2) In empowering blind people, Pertuni implements several strategies such as learning Braille, playing music and talking computers. (3) The obstacles faced in implementing these strategies are: Accessibility, Facilities, and Psychological (4) Sourced from SWOT analysis research, DPD Pertuni shows that it is located in an aggressive or growing position on the strategy (SO). Where in this position has a strong position and describes the existing external opportunities and avoids the potential negative effects of threats.